Case reportOmalizumab as a new therapeutic approach for children with severe asthma - Jerzyńska, Joanna; Sztafińska, Anna; Woicka-Kolejwa, Katarzyna; Stelmach, Iwona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Omalizumab has been shown to improve asthma control when added to a regimen of guideline-based therapy for inner-city children and adolescents, nearly eliminating seasonal peaks in exacerbation and reducing the need for other medications to control asthma. Below, we describe a case of a 17-year-old non-smoker with a history of severe asthma admitted to our clinic after unsuccessful 10-year immunotherapy. The patient fulfilled the criteria for anti-IgE therapy, he was prescribed omalizumab 600 mg every 2 weeks. During therapy he was able to reduce his use of ICS and did not require any oral corticosteroids. He experienced an increase in his ability to exercise and noted no exacerbation of asthma symptoms. It is possible that in our patient, specific immunotherapy could be successfully continued after the initiation of omalizumab therapy.